Efficiency analysis of distributed power combining for mobile platform - Wenbo GUO; Jiaxin DU; Jian YANG; Mu YAN; Hongzhi ZHAO; Shihai SHAO (Tongxin xuebao)
Aiming at the position perturbation of mobile platform, the impact of position perturbation was analyzed on distributed power combining efficiency.The model of distributed power combining with position perturbation was established, and the average far-field beampattern, complementary cumulative distribution function (CCDF) expressions and the approximate expression of 3 dB beamwidth were derived.The results show that intensified position perturbation can lead to continuous deterioration of the average far-field beampattern, peak power, 3 dB beamwidth, and CCDF of distributed power combining.When the position perturbation reaches 9% of the signal wavelength, the signal peak power of the mobile platform after distributed power combining decreases to 90% of its theoretical upper limit.